المضمون التربوي للدرس العقدي كتاب الفتح الرباني والفيض الرحماني للشيخ عبد القادر الجيلاني باب الإلهيات أنموذجا. - يسرى, اوليدي (جامعة الوادي university of eloued, 2023)
"انطلاقًا ممّا تمثّله العقيدة في حياة المسلمين؛ فهي الأساس الذي تقوم عليه أفعالهم وسلوكاتهم، ونظرًا لغياب دور العقيدة وانطفاء شعلة الإيمان في حياتهم، بسبب التحدّيات المعاصِرة (مِن غزو فكري وثقافي، وعولمة...)، فقد جاءت هذه الدراسة للتّأكيد على دور العقيدة في تربية النفوس، وضرورة إحياء شعلة الإيمان في القلوب، من خلال إبراز المضامين التربوية للدرس العقدي -باب الإلهيات أنموذجًا-، استقراءً من كتاب ""الفتح الرباني والفيض الرحماني"" للشيخ عبد القادر الجيلاني. فتناولنا فيها الثمراتِ التربويّةَ للإيمان بالله والإيمان بالقضاء والقدر على مستوى النفس والمجتمع، من خلال استنباط آراء الجيلاني فيها وتحليلها. ومن أهم النتائج التي توصّلنا إليها: - شمولية الإيمان لجميع مناحي الحياة، وضرورة تفعيله فيها خاصة الجانب التربوي منها. - أن الأمة الإسلامية –فردًا وجماعةً- إذا تحقّقت بثمرات الإيمان وعَمِلت بها، تَصِل إلى السعادة والنصر والتمكين –بإذن الله-. ""The Islamic creed is the basic fondation on which Muslim’s actions and behavior are based. However, due to contemporary challenges (cultural, intellectual and globalization invasion),the of tame of faith, has been extinguished in the hearts of many Muslims. Therefore, this study emphasizes the rote of Islamic creed in the purification of the soul. and the necessity of surviving the flame of faith in it, this is done through highlighting the educational contents of faith and believing lesson, (the divinities part as a model) extrapolation from the book of “El- FATEH ELRABBANI oua EL- FAID EL- RAHMANI” written by EL- CHEIKH ABD EL KADER AL DJILANI, where we dealt with the following results and benefits of (EL Iman) believing in god and disteny, theism (faith in god), fatalism (faith and justice), at the level of soul and society by taking into consideration EL DJILANI’S ideas and analysis. The main consequences are as follow: faith includes all aspects of life the necessity of activating faith in our life especially in the purification aspect. If the Islamic nation follow: the results of the Islamic creed and faith, it will achieve happiness victory and empowerment (success). "
عقيدة
Keywords: المضمون- التربية- العقيدة- الشيخ عبد القادر الجيلاني- كتاب الفتح الرباني- الإلهيات.; Content- Education- The creed- CHEIKH ABD EL KADER AL DJILANI- book of “El- FATEH ELRABBANI- the divinities